PENGARUH NILAI NASABAH DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH (Studi Kasus Pada Bank Bri Cabang Martadinata Malang) - Adinda Putri Ramadhani; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACThis study aims to analyze and discuss customer value, service quality and customer satisfaction. The population consists of 550 and the sample consists of 85 consumers. Data collection in this study through a questionnaire. Data analysis in this study uses SPSS version 14. Testing the application of data used in this study include multiple regression analysis, validity test, reliability test, normality test, classic assumption test, and research hypothesis test. Partially the customer value variable does not have a significant effect on the BRI customer satisfaction variable of the bank martadinata Malang branch. While service quality variables have a significant effect on customer satisfaction at BRI Malang Martadinata branch. That there is a simultaneous effect of variable customer value and service quality on customer satisfaction at the BRI branch of the Martadinata branch in Malang.Keywords: Customer Value, Service Quality, Customer Satisfaction